The Effectiveness of Venopheric Infusation on Feritine Levels in Pregnant Women with Iron Deficiency Anemia in RSPAD Gatot Soebroto - Nopiah, Ida; Nofa Anggraini (STIKep PPNI Jawa Barat, 2022)
Aims: In normal pregnancies accompanied by nausea, parenteral iron is seen as an attractive option for IDA therapy and is becoming more popular because of newer intravenous iron preparations with better side effects compared to older preparations, which allow high doses of iron to be administered. given rapidly in one treatment. The purpose of this study was to determine the effectiveness of Venofer infusion on ferritin levels in pregnant women with iron deficiency anemia at Gatot Soebroto Hospital in 2022. Methods: Quasi experimental research method with to one group pretest posttest design. The instrument uses Standard Operating Procedures for giving Venofer Transfusion. The sample technique used total sampling, a sample of 46 respondents. Univariate analysis showed the distribution of Iron Deficiency Anemia, Bivariate T test analysis. Results: This study found a significant difference from Iron Deficiency Anemia before and after administration of Venofer infusion. Conclusion and Suggestion: So that the administration of Venofer infusion can increase Ferritin levels in pregnant women with iron deficiency anemia. There is a difference in the average increase in Ferritin levels between before and after administration of Venofer infusion.